TOMATO (Solanum esculentum Mill.) YIELD AND NUTRITIONAL TRAITS ENHANCEMENT AS AFFECTED BY BIOCHAR, ORGANIC AND INORGANIC FERTILIZERS - Seyed Mahdi Nabaei; Mohammad Reza Hassandokht; Vahid Abdossi; Mohammad Reza Ardakani (Acta Scientiarum Polonorum: Hortorum Cultus, 2021)
This experiment studied the effects of biochar and chicken manure tea compost on growth, productivity, and nutritional traits of tomato (Solanum esculentum MILL). A factorial based experiment within complete randomized block design with three replications was conducted to evaluate the traits. The results showed that the biochar + chemical fertilizer (TIB1) contained the significantly highest values of soil EC (1.81 dsm–1), total N (0.39%), available P (156.92 ppm), available K (442.22 ppm), leaf N (3.54%), leaf K (6.73%), and shoot dry weight (463 g). The treatment of (TIB1) increased the production of tomatoes by 393.9% above the control soil conditions. Signiﬁcant differences in fruit quality were observed. The biochar + chicken manure compost tea (1 : 4) (T3B1) treatment contained the highest values of total polyphenols (378.83 mg) and vitamin C (29.03 mg/100 g–1), it but did not significantly affect total soluble solid and titratable acidity values on average compared with control conditions. However, the application of biochar at 10 tons ha–1 cannot fully substitute for fertilizers. Therefore, nutrition management can be achieved by biochar plus inorganic and organic fertilizer to increase tomato productivity and quality, respectively.